The Influence of Social Media and e-WOM on Purchase Intention and Brand Image in Online Shops: An Empirical Study on Online Shop Consumers in Indonesia - Faridzie, Muhammad Robby Reynaldy Al; Widodo, Arry (Journal of International Conference Proceedings, 2023)
The purpose of this study is to examine the influence of social media and e-WOM on purchase intention and brand image in online shops in Indonesia. An empirical study was carried out using data from online shop consumers in Indonesia through an online questionnaire. The sample used was 384 respondents chosen by the use of purposive sampling. Data analysis was performed using the SEM-PLS technique. According to research, social media and e-WOM have a substantial impact on purchase intent and brand perception in Indonesian online stores. Furthermore, at present the internet is a part that is often used by the general public, so social media and e-WOM have an important role in influencing consumer behavior in buying products at online shops. The managerial implication of this research is that online retailers must be mindful of their use of social media platforms and e-WOM as effective marketing strategies to increase buying interest and brand image of their products in the online market in Indonesia.